Comparative Analysis of Clinical Effects of Insulin Aspart Combined with Acarbose and Metformin in the Treatment of Diabetes Mellitus. (8th July 2022) - Jin, Hongmei; Zhang, Hongyun
Abstract : Objective . To investigate the clinical effect of Insulin aspart 30 combined with acarbose and metformin enteric-coated tablets in the treatment of diabetes mellitus. Methods . 90 diabetic patients admitted to our hospital from January 2019 to December 2021 were selected as the research subjects, and the patients were randomly divided into group A ( n  = 30, using insulin aspart 30 alone), group B ( n  = 30, using insulin aspart 30 combined with metformin enteric-coated tablets), and group C ( n  = 30, using insulin aspart 30 combined with acarbose). The blood glucose balance before meals and before going to bed was maintained in the three groups of patients, and the blood glucose fluctuations, time to target, hypoglycemia, insulin dosage, and daily consumption of the three groups were compared. Results . There was no significant difference in blood glucose and average blood glucose at each time point before treatment in the 3 groups of patients (P > 0.05 ); compared with the blood glucose and average blood glucose at each time point after reaching the target in the three groups, the blood glucose after dinner in group A was significantly higher than that in groups B and C; at 2 : 00, the blood glucose of group A was significantly higher than that of group B (P < 0.05 ); there was no significant difference in blood glucose and average blood glucose at other time points (P > 0.05 ). There was no significant difference in blood glucose standard deviation, LAGE, and PPGE at each point in the three groups before treatment (P > 0.05 ); the standard deviation of blood glucose, LAGE, and PPGE at each point of the three groups of patients after reaching the standard were compared with those in the same group before treatment, and the differences were statistically significant (P < 0.05 ); there were statistically significant differences in blood glucose standard deviation, LAGE, and PPGE among the 3 groups after reaching the standard (P < 0.05 ). Compared among the three groups, the standard deviation of blood glucose and LAGE level at each point after reaching the standard, the difference between group B, group C, and group A was statistically significant (P < 0.05 ); however, there was no significant difference between the patients in group B and group C (P > 0.05 ); the level of PPGE in group A was higher than that in group B, which was higher than group C, and between group C and group A, the difference was statistically significant (P < 0.05 ). The time of reaching the standard in 3 groups was statistically significant (P < 0.05 ); there was no significant difference in the time of reaching the standard between group B and group C (P > 0.05 ). There was no significant difference in the incidence of hypoglycemia among the 3 groups (P > 0.05 ); there were significant differences in the proportion of insulin twice a day among the three groups (P < 0.05 ); there were statistically significant differences in daily insulin dosage among the 3 groups after reaching the standard (P < 0.05 ). The daily consumption of the three groups of patients after reaching the standard was compared, the difference was statistically significant (P < 0.05 ), and there was no significant difference between group A and group B (P > 0.05 ). Conclusion . The effect of insulin aspart 30 alone in the treatment of diabetic patients is not good, it will lead to a large fluctuation of blood sugar in the patient's body, and the time required to reach the standard is relatively long; the use of insulin aspart 30 combined with metformin enteric-coated tablets or acarbose can effectively reduce the blood sugar fluctuation range of diabetic patients and reduce the number of insulin injections, and insulin aspart 30 combined with metformin en teric-coated tablets can also greatly reduce the daily insulin dosage and daily consumption cost of diabetic patients.